ترتيب الكليّات الضروريّة للشريعة عند الأصوليين : دراسة تحليلة نقدية - علي، حاج داود عمر بهون (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The present research revolves around the topic of classification of the Shari'ah five necessary universals (al-kulliyyat al-daruriyyah) according to the classical and contemporary Muslim scholars. For this our attention was focused on displaying the bases or criteria they relied upon in classifying those universals and the patterns or schemes of classification they suggested, as well as on explaining the reasons behind their differences therein. To pave the way for the treatment of the different aspects of the subject, it was necessary to address the fundamental question as to whether the classification of the Shari'ah necessary universals one way or the other is needed or necessary in the first place. Due to the complex nature of the subject, the researcher made use of a set of methods consisting mainly of induction -for the opinions of the scholars-, with analysis, and comparisons, and a clear evaluative and critical orientation whenever required. The study came up in four chapters, the first one presented the study plan, while the second chapter focused on determining the meanings of the research keywords, and the classification possibility with its significance and its discovering methods, also searching the suggestions which related to the classification schemes. Furthermore, we searched on the third chapter the classification bases according to the classical Muslim scholars, and the reasons behind their differences. Then, we addressed on the last chapter the same elements according to the contemporary Muslim scholars, with highlighting their important contributions on the subject. The study has arrived at a number of findings the most important of which can be summarized in the following points: the possibility of and the need for the classification of the Shari'ah necessary universals; adopting multiple bases or criteria of classification is preferable to using one single criterion. The study has also shown that al-Ghazali's classification (religion, life, intellect, progeny and property) is the basis for all other classifications, without this meaning blind using thereof in all practical situations as certain circumstances and emergent issues might require breaking away from this classification and adopting other patterns in which some of those universals may be given priority over others preceding them. Finally, the study has shown that to the extent to which it is possible to bridge the gap between the different views of early scholars regarding the classification of Shari'ah necessary universals, this has proven difficult as far as contemporary scholars are concerned.